FIRST LEVEL OF PROTEROZOIC CALCAREOUS CONCRETION FORMATION IN THE NORTHEASTER PART OF THE BALTIC SHIELD - Melezhik V.A. (My University, 1987)
Carbonate concretions yield the most data for reconstruction purposes because they are compositionally very diverse and have compositions very similar to those of the physicochemical medium in which they were formed. The most abundant carbonate concretions are found in Phanerozoic and Holocene sedimentary complexes, but there are few in Precambrian metamorphic rocks. A few calcareous concretions had been found in the metasediments of the Kola Peninsula, specifically in the Imandra-Varzuga complex. Golubev and associates also reported the presence of carbonate concretions in rocks of the Pechenga complex. This paper reports on thick Precambrian sequence with widespread carbonate concretions which were found in rocks of the Pechenga complex as a result of a systematic lithologic study of metamorphic formations in the northeastern part of the Baltic shield.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой